Portrait of Gustav Heinrich Johann Apollon Tammann
Postcard featuring a photograph of Gustav Heinrich Johann Apollon Tammann (1861-1938). Tammann was a Baltic German physical chemist. He worked in the fields of metallurgy and studied the physical properties of metals and their alloys.
Keywords: Tammann, Gustav Heinrich Johann Apollon, 1861-1938; Chemists